Abel Cahen's Open City: A Theoretical Inquiry into Urban Complexity and the Limits of Control. Issue 2 (2nd July 2016) - Domínguez, Guiomar Martín
Abstract : Abel Cahen's graduation project (University of Delft, 1970) envisioned an alternative approach to urban design that proposed to engage with complexity and uncertainty as primary foundations of the architect's task. Inspired by the 1960s revisionist attitude, Cahen worked with a series of abstract activity diagrams that appear chaotic but are based on highly coherent geometric structures. This essay endeavors to rescue Cahen's project, which has been disregarded by scholars as a mere formal game, from historical oblivion and present it as a radical theoretical manifesto that reflects upon the architects' available tools to handle complexity, while recognizing the risks and limitations of strictly rational design processes.